Modeling families of public licensing services: a case study - Cledou, Maria Guillermina (2017)
Software Product Lines (SPLs) enable the development of families of software systems by taking advantage of the commonalities and variabilities of the members of the family. Despite its many advantages, it is an unexplored area in the electronic government domain, an area with evident families of services, and with high demands to develop faster and better services to citizens and businesses while reducing costs. This paper discusses the need of formal methods to model SPLs for such domain. It presents a case study of a family of public licensing services modeled in UPPAAL and based on Featured Timed Automata, an extension of Timed Automata to model realtime SPLs. It analyzes the suitability of FTA to model distributed families of services, while provides hints on a possible enrichment of FTA to better support modularization and compositionality of services.